Anxiety and clenching as contributing factors of recurrent aphthous stomatitis - Wiwik Mayanti; Febrina Rahmayanti; Siti Aliyah Pradono (Wolters Kluwer Medknow Publications, 2019)
Background: Recurrent aphthous stomatitis (RAS) is a common oral mucosa disease. Anxiety plays a role in the development of RAS, as it can lead to parafunctional oral habits such as bruxism (teeth grinding or jaw clenching) that may injure the mucosa, and this physical trauma can trigger ulceration in susceptible individuals with RAS. This case report describes the parafunctional oral habits caused by anxiety as the contributing factors of RAS. Case Report: A 17-year-old female came to the Dental Hospital, Faculty of Dentistry, Universitas Indonesia, with the complaints of ulcers at the lateral aspect of the tongue for 4 days since the tongue was bitten while she was sleeping. From the patient history, clinical evaluation, and investigation of the questionnaire, we detected a bruxism habit. We assumed that clenching was a contributing factor for the ulcers in this case. Intra-oral examination revealed two irregular ulcers of about 3 mm and 0.5 mm that were surrounded by erythematous halos and were yellow at the floors of the 46 and 36 teeth. The patient completed the Hospital Anxiety and Depression Scale and the Hamilton Rating Scale for Anxiety; the results of both were moderate anxiety. The management we suggested to the patient to control the anxiety was referral to a psychologist and an orthodontist; we gave chlorhexidine 0.2% to compress the lesions three times a day. Conclusion: Anxiety can produce a parafunctional oral habit that is a contributing factor of RAS. Coping with anxiety is needed to improve the clenching activity and RAS.